The cyclicality of leverage - Tobias Adrian; Nina Boyarchenko; Hyun-Song Shin (Federal Reserve Bank of New York, 2015)
This paper studies the question of the economic scale of financial institutions. We show that banks actively smooth book equity by adjusting payouts to achieve a desired trajectory of book equity. The countercyclical nature of net payouts of financial institutions leads to procyclical book leverage, while market leverage is nearly entirely reflective of movements in book-tomarket ratios. There is an apparent structural break after the 2008 crisis, indicated by the banking sector's subdued growth rate relative to pre-crisis levels. Market volatility dampens the intermediary leverage cycle. We draw conclusions for theories of financial intermediation and for capital regulation.
Keywords: E02; E32; G00; G28; 330; financial intermediation; market volatility; macro-finance